Comparative study of decompression events in traditional divers and modern divers - Yusnaini Siagian; Linda Widiastuti; Soni Hendra Sitindaon; Utari Yunie Atrie; Liza Wati (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Decompression can occur due to decreased pressure when the diver rises to the surface, releasing gases from solutions, especially nitrogen, in the tissues and blood, forming bubbles in the blood. The formation of air bubbles can block blood flow and nerves. It will cause symptoms of joint pain, headaches, itching, numbness, paralysis, and even death. Decompression is one of the diseases caused by diving. This study compared decompression events in traditional divers with modern divers in the Kawal area, Gunung Kijang District, Riau Islands. The research design was conducted comparatively with a sample size of 25 traditional and 25 modern divers. The sampling technique used a random sampling technique. The results showed no difference in the incidence of decompression in both traditional divers and modern divers in the Kawal area, Gunung Kijang District, Riau Islands. Most respondents have experienced decompression events, both traditional and contemporary divers. However, there is a tendency for traditional divers to experience decompression events 1.136 times compared to modern divers. Decompression events can occur in all traditional and professional or contemporary divers. In addition to knowing the safety and security of diving, divers must also pay attention to their health conditions.